2013
DOI: 10.5539/jas.v5n4p224
|View full text |Cite
|
Sign up to set email alerts
|

Radical Scavenging Capacity and Antioxidant Activity of the Vitamin E Extracted from Palm Fatty Acid Distillate by Sequential Cooling Hexane

Abstract: The radical scavenging capacity and antioxidant activity of the vitamin E extracted from palm fatty acid distillate by the sequential cooling hexane were compared to those of the synthetic antioxidants including butylated hydroxyanisole (BHA), 2,6-di-tert-butyl-4-methylphenol (BHT), pyrogallol (PG), tert-butylhydroquinone (TBHQ) and commercial α-tocopherol. The extracted vitamin E contained 2,509. 57, 9.24, 157.85, 6.70, 1,779.92, 3.97, 2,376.38, 818.80 and 7,662.45 ppm of α-, β-, γ-, δ-tocopherol and α-, β-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…β-T3 content progressively decreased in all samples and was undetectable after 90 days of storage. β-T3 is more sensitive and susceptible to oxidation compared to α-T likely in relation to the presence of three, rather than two unsaturations [52]. A similar trend was observed by Durante et al [6,8], who evaluated the stability of different tocochromanol forms in vegetable oils.…”
Section: Resultsmentioning
confidence: 65%
“…β-T3 content progressively decreased in all samples and was undetectable after 90 days of storage. β-T3 is more sensitive and susceptible to oxidation compared to α-T likely in relation to the presence of three, rather than two unsaturations [52]. A similar trend was observed by Durante et al [6,8], who evaluated the stability of different tocochromanol forms in vegetable oils.…”
Section: Resultsmentioning
confidence: 65%
“…Power is an indicator of the reduction of an antioxidant compound [19]. In this case, the reducing power is measured by an antioxidant's ability to convert Fe 3+ into Fe 2+ [20]. Compounds that have reducing power may be able to act as antioxidants because they can produce electrons or hydrogen atoms so that radical compounds turn out to be more stable.…”
mentioning
confidence: 99%
“…According to the GC-MS results of the extract of Cu. reflexa grown on Co. grandis, the presence of methyl ferulate and vitamin E, which are already known to possess high antioxidant activities [20][21], may be related to the greater antioxidant activities. Moreover, previous research reports have revealed that phenolic compounds can exhibit high antioxidant activity [22][23], especially rutin, catechin and quercetin, which were found in the extracts of Cu.…”
mentioning
confidence: 99%